Lessons Learned Adapting and Implementing Another Organization’s Program to Promote Healthy Aging - Erin Jewell; Theresa Serio; Karen Basinger; Jennifer Dixon Cravens; Lisa McCoy; Mona Habibi; Shauna C. Henley (Journal of Human Sciences and Extension, 2023)
Programming which promotes healthy aging may be lacking in states where nutrition and health interventions are directed earlier in life. Due to Maryland’s increasing aging population, a team of 10 University of Maryland Extension Family and Consumer Sciences educators received permission to adapt and implement the Iowa Department of Public Health’s, in partnership with the Iowa Department of Human Services and Department on Aging, Fresh Conversations program to fit the needs of Maryland’s older adults. The purpose of this manuscript is not to discuss research findings but rather to share our challenges, successes, and recommendations for adapting and implementing another state’s multi-session program to meet the needs of individual states’ communities. Specifically, we discovered communicating with partnering sites, offering food tastings, accommodating various food cultures/traditions, following the original program design, and efficiently collecting data or programmatic form responses needed careful consideration. Despite the challenges we encountered, we expanded our national and state partnerships; reached 2,836 educational contacts across the state; and developed a detailed planning, implementation, and evaluation protocol and training, which is being used as a template for other statewide program efforts.